2012
DOI: 10.1186/1472-6963-12-314
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between quality of work life and turnover intention of primary health care nurses in Saudi Arabia

Abstract: BackgroundQuality of work life (QWL) has been found to influence the commitment of health professionals, including nurses. However, reliable information on QWL and turnover intention of primary health care (PHC) nurses is limited. The aim of this study was to examine the relationship between QWL and turnover intention of PHC nurses in Saudi Arabia.MethodsA cross-sectional survey was used in this study. Data were collected using Brooks’ survey of Quality of Nursing Work Life, the Anticipated Turnover Scale and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
213
11
17

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(271 citation statements)
references
References 59 publications
(85 reference statements)
30
213
11
17
Order By: Relevance
“…According to many scholars, the quality of the job is an indicating factor which influences performance [33,55]. Consequently, the hospital administrators must push nurses' performance forward to a high level of competency through provision of an exemplary work climate that allows nurses to share ideas, team spirit and creativity.…”
Section: Resultsmentioning
confidence: 99%
“…According to many scholars, the quality of the job is an indicating factor which influences performance [33,55]. Consequently, the hospital administrators must push nurses' performance forward to a high level of competency through provision of an exemplary work climate that allows nurses to share ideas, team spirit and creativity.…”
Section: Resultsmentioning
confidence: 99%
“…HİYKÖ'den alınan toplam puanın artması hemşirele-rin iş yaşamı kalitesinin yüksek olduğunu, azalması ise hemşirelerin iş yaşamı kalitesinin düşük olduğunu göstermekte-dir. Çalışmada kullanılan HİYKÖ aralarında İran, İngiltere ve Suudi Arabistan ülkelerinin de bulunduğu yurtdışı hemşire-lik çalışmalarında kullanılmıştır (11,14,20).…”
Section: Tanıtıcı öZellikler Formuunclassified
“…The study found that there are two principal reasons why Turnovers occur in the industrial sector in the country under study: the work environment, and salary. Work environments should be improved and the money offered to employees should be increased to limit turnovers [35]. Work Stress and its Impact on Working Turnover for the Workers in Border Guards Centers in Eastern Region (K.S.A): This study aims at understanding how work pressure affects turnover at Border Guards' centers.…”
Section: Literature Reviewmentioning
confidence: 99%